Classroom Management and Deep Learning: How Facility Design and Student Organization Shape Collaborative Behavior - Zainuddin Zainuddin; Asmoni Asmoni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyse the contributions of these two dimensions to the development of students' collaborative behaviour and the achievement of deep learning. This study used a quantitative, cross-sectional survey design with 287 elementary school teachers. Data were collected using a 40-item Likert-scale questionnaire and analysed using Pearson's correlation, multiple linear regression, and Baron and Kenny's mediation analysis. The results showed that students' collaborative behaviour was the strongest predictor of deep learning (β = 0.42, p < 0.001) and acted as a significant mediator between the classroom management dimensions and learning outcomes. Environmental and instructional classroom management had a direct influence on deep learning, which was further strengthened through the mediation of collaborative behaviour. The novelty of this study lies in the development of an integrative mediation model that combines environmental and instructional classroom management with collaborative behaviour as the main mechanism for bridging classroom management practices and deep learning. The implications of this research emphasise the need for teachers to design classes that encourage collaboration through group work, directed discussions, and shared responsibility to support meaningful, in-depth learning.